39. Efficacy of Jatropha cream (Jatropha curcas L.) on maturation phase of cutaneus healing process in Mice (Mus Musculus) - Abdul Harris; Cut Mentari Fatihah Amran; M. Nur Salim; Ummu Balqis; T. Armansyah; T. Fadrial Karmil; Ginta Riady (Universitas Syiah Kuala, 2019)
This study aims to determine the efficacy of jatropha curcas L. cream in the maturation phase of healing of mice leather injuries. This study used nine rats with 3 treatments, ie treatment group I smeared cream base (P1), treatment group II smeared 0.1% sulfadiazine cream (P2) and treatment group III smeared jatropha curcas 10% (P3). The result of ANAVA test of treatment I, treatment II and treatment III had significant effect (P 0,05) on fibroblast cells but each treatment group on collagen density level showed significant effect (P 0.01). Duncan test results on fibroblasts, P3 was significantly different (P 0.05) with P2 and P3, whereas the results on P3 collagen density were significantly different (P 0.01) with P2 and P1. The conclusion that 10% jatropha gum cream for 10 days can decrease the number of fibroblast cells and increase the amount of collagen thus accelerate the process of maturation phase of healing of mice leather injuries.